Estudio de los indicadores de calidad de un sistema de riego por aspersión subfoliar en Banano (musa aaa) en la zona de Puebloviejo - Tandazo Garcés, Juan Ernesto (2015)
This research December 2014 was established in the premises of the Ranch Naranjo Chico, owned by Dr. Juan Manuel Costa, located in the town Puebloviejo province of Los Ríos in UTM coordinates 663660, 9833233 according to the ellipsoid PSAD 56. The test consisted of evaluating a module 126 formed by sprinkler irrigation, sprinklers and lateral spacing of 12 x 12 meters. Uniformity of distribution, uniformity coefficient, factor adequacy of irrigation application efficiency, properly irrigated area: the variables were evaluated. All variables were analyzed with descriptive statistics and based on that analysis concluded: The module has performance problems because judging by the results of the evaluation, variations in pressure and flow rates exceed the permissible limits as the foundation of hydraulic pipe.........